Photoacoustic phasoscopy for tissue characterization - Gao, Fei (2013)
In this paper, a novel method named photoacoustic `phasoscopy' (PAP) is proposed to collect both scattered photons and induced photoacoustic wave to build a photo-acoustic phase spectrum, rather than conventional frequency spectrum, for biological tissue characterization,. PAP provides phase contrast with enhanced sensitivity and robustness compared with pure optical or photoacoustic sensing only. Experimental result of characterizing three different kinds of biological tissues proves the feasibility of PAP for potential biomedical sensing and imaging applications.